2015
DOI: 10.1111/mmi.12983
|View full text |Cite
|
Sign up to set email alerts
|

Yap7 is a transcriptional repressor of nitric oxide oxidase in yeasts, which arose from neofunctionalization after whole genome duplication

Abstract: SummaryFlavohemoglobins are the main detoxifiers of nitric oxide (NO) in bacteria and fungi and are induced in response to nitrosative stress. In fungi, the flavohemoglobin encoding gene YHB1 is positively regulated by transcription factors which are activated upon NO exposure. In this study, we show that in the model yeast Saccharomyces cerevisiae and in the human pathogen Candida glabrata, the transcription factor Yap7 constitutively represses YHB1 by binding its promoter. Consequently, YAP7 deletion conferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 82 publications
2
79
0
Order By: Relevance
“…We observed that the absence of Hap5 totally abolished Yap5 binding to its target. In a previous work, we noticed that Yap5 contains a degenerated but still recognizable Hap4L motif just upstream of its bZIP domain 21 . This motif corresponds to the N-terminal half of the canonical Hap4L domain (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…We observed that the absence of Hap5 totally abolished Yap5 binding to its target. In a previous work, we noticed that Yap5 contains a degenerated but still recognizable Hap4L motif just upstream of its bZIP domain 21 . This motif corresponds to the N-terminal half of the canonical Hap4L domain (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…In S. cerevisiae and C. glabrata , iron stress response has been shown to be controlled by the Yap5 bZIP transcription factor 21, 3436 . This regulation absolutely requires the direct binding of Yap5 to YRE motifs (TTACTAA) in the promoters of these genes 29, 34, 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations